Takotsubo cardiomyopathy in a patient with lung adenocarcinoma - (:unkn) unknown (My University, 2012)
Takotsubo cardiomyopathy (TC) is a rare and usually physical or emotional stress-induced clinical disorder characterized by transient left ventricular dysfunction and apical segment ballooning. Much is still unknown regarding risk factors and clinical relationships. Recently, an association between TC and malignancies has been proposed. We present a case of lung adenocarcinoma whose initial hospital admission was due to TC. We contribute this case report to the growing set of literature on the association between TC and malignancies.
Keywords: Cardiac dysfunction; lung adenocarcinoma; takotsubo cardiomyopathy